Studies On Customer Service Quality Management In Schools Using The DMAIC - Ahmad Tajudin, Mohd Khairil Amri; Nurul Huda Juwaini (Jurnal Kejuruteraan, Teknologi and Sains Sosial (JKTSS), 2024)
Customer satisfaction is important and critical issue not only in industry but also in all educational institutions. Parents, students and community members who act as a client to a school has their own requirements to be met by the school management. The purpose of this study is to examine the extent of customer satisfaction improved in schools capable of using a variety of DMAIC tools. A variety of services are offered by the school to its customers. The scope of the study is more geared to the services offered to students who are experiencing health problems. There are numerous of DMAIC tools used by researchers to speed up the delivery process in schools as SIPOC, flowchart, Fishbone diagrams and so on.